PENGARUH MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTUAN LUDO MAGNET TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD - Arfaiza, Shafina Alya; Hafiziani Eka Putri; Erna Suwangsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on students' low mathematical problem solving abilities. One effort that can improve this situation is by using the Teams Games Tournament (TGT) type cooperative learning model. The aim of this research is to determine the differences in the improvement and influence of students' mathematical understanding abilities using the Teams Games Tournament (TGT) type cooperative learning model assisted by ludo magnets and students using the conventional learning model with a scientific approach in class IV students at SDN Mekarjaya 28. The type of research used is quasi-experimental or quasi-experimental research. The design of this research is a non-equivalent control group design by providing an initial ability test, namely a pretest and a final ability test, namely a posttest, after being given treatment in the two classes that have been determined. The samples chosen in this research were 20 students in class IV A and 20 students in class IV B. The instruments used in this research were tests and non-tests. The results of the research show that the difference in increasing mathematical problem solving abilities of class IV A students who study using the Teams Games Tournament (TGT) type cooperative learning model get better results compared to class IV B students who study using conventional learning models with a scientific approach. There is also an influence of implementing the Teams Games Tournament (TGT) type cooperative learning model on students' mathematical problem solving abilities in mathematics learning in elementary schools. Looking at the results obtained, the Teams Games Tournament (TGT) type cooperative learning model can be used as an alternative to be used in the classroom learning process so that the learning carried out is more enjoyable and more meaningful. Keywords: ludo magnet media, students mathematical problem solving ability, teams games tournament type cooperative model